2004
DOI: 10.1111/j.1365-2893.2004.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms of steatosis in hepatitis C virus genotypes 1 and 3 infections

Abstract: This study reports evidence that hepatocellular steatosis, a frequent histological feature of chronic hepatitis C, is principally metabolic in hepatitis C virus (HCV) genotype 1-infected patients, whereas it is principally virus-induced in HCV genotype 3-infected patients. Multivariate analysis of data on 176 patients with chronic hepatitis C revealed that the severity of steatosis was independently related to HCV RNA load alone in patients infected by HCV genotype 3, whereas it was independently related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 28 publications
5
62
0
2
Order By: Relevance
“…The association between LS and genotype 3 presumably due to the direct action of HCV [35,36] was also confirmed by both univariate and multivariate analysis. Besides, only in patients with genotype 1, LS was correlated with high BMI and past history of alcohol intake exceeding 50 g/day, in agreement with the pathogenic mechanism of steatosis, principally metabolic, postulated in the patients with this genotype [37]. As regards the correlation between histological steatosis and sonographic findings of steatosis, when all grades of hyperechogenicity were globally considered, BLP showed a relatively high sensitivity for LS (75 %), while the specificity was low (50 %), for the presence of a high number of false positives for LS in the patients with BLP grade 1.…”
Section: Resultssupporting
confidence: 80%
“…The association between LS and genotype 3 presumably due to the direct action of HCV [35,36] was also confirmed by both univariate and multivariate analysis. Besides, only in patients with genotype 1, LS was correlated with high BMI and past history of alcohol intake exceeding 50 g/day, in agreement with the pathogenic mechanism of steatosis, principally metabolic, postulated in the patients with this genotype [37]. As regards the correlation between histological steatosis and sonographic findings of steatosis, when all grades of hyperechogenicity were globally considered, BLP showed a relatively high sensitivity for LS (75 %), while the specificity was low (50 %), for the presence of a high number of false positives for LS in the patients with BLP grade 1.…”
Section: Resultssupporting
confidence: 80%
“…A number of studies have found an association between steatosis and fibrosis stage (1)(2)(3)(4)(5)(6)(7), or between steatosis and necroinflammation in chronic HCV infection (8). Others have found an association between genotype 3 and hepatic steatosis (1,2,(5)(6)(7)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Distinct genotype-specific pathogenic mechanisms appear to underlie the steatosis in CHC. In HCV genotype 3 infection, [7][8][9][10][11][12][13][14] steatosis is often of moderate to severe intensity, correlates with the levels of intrahepatic viral replication, 7,9,10,12,15,16 and largely resolves after successful antiviral therapy. 9,10,15,17,18 Steatosis may recur on virologic relapse.…”
mentioning
confidence: 99%
“…9,10,15,17,18 Steatosis may recur on virologic relapse. Host factors, principally those associated with insulin resistance (IR) and its clinical attributes (obesity and T2DM), 7,[10][11][12]16,19,20 are responsible for the development of steatosis in non-genotype 3 HCV, and steatosis does not ameliorate with antiviral therapy in these patients. 15,18,20 Host variables such as age at infection, 7,11,[21][22][23][24][25][26] the duration of infection, 21,24 male gender, [21][22][23] and excessive alcohol intake 7,11,[21][22][23]27,28 are well-established correlates of advanced hepatic fibrosis in CHC.…”
mentioning
confidence: 99%